Atomic force microscopy study of ionomycin‐induced degranulation in RBL‐2H3 cells. Issue 6 (3rd February 2016) - Pi, Jiang; Huang, Lufen; Yang, Fen; Jiang, Jinhuan; Jin, Hua; Liu, Jianxin; Su, Xiaohui; Wu, Anguo; Cai, Huaihong; Yang, Peihui; Cai, Jiye
Summary: Mast cell degranulation is the typical anaphylaxis process of mast cells associated with the release of cytokines, eicosanoids and their secretory granules, which play very important roles in the allergic inflammatory response of the human body upon anaphylactogen stimulation. The calcium ionophore ionomycin is widely used as a degranulation induction agent for mast cell degranulation studies. In the present work, ionomycin‐induced degranulation of RBL‐2H3 basophilic leukemia cell line cells was investigated in vitro by high resolution atomic force microscopy (AFM). Ionomycin, which could increase the intracellular free Ca 2+ level and β‐Hexosaminidase release, was found to induce the formation of a kind of peculiar vesicles in the cytoplasm area of RBL‐2H3 cells. Those vesicles induced by ionomycin would desintegrate to release a larger amount of granules surrounding RBL‐2H3 cells by the controlling of F‐actin. These results provide the precise morphological information of ionomycin‐induced mast cell degranulation at nanoscale, which could benefit our understanding of ionomycin‐induced mast cell anaphylaxis model and also validate the applicability of AFM for the detection of allergic inflammatory response in mast cells. SCANNING 38:525–534, 2016. © 2016 Wiley Periodicals, Inc.